Angiotensin converting enzyme 2 (ACE2), COVID-19 and cardiac injury: what cardiologist should know - Sidhi Laksono; Budhi Setianto; Steven Philip Surya (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Coronavirus disease 2019 (COVID-19) has already stated as a pandemic by the World Health Organization (WHO). Until now, Indonesia has also infected with this severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections. All medical staffs join hand by hand to overcome this pandemic, not only pulmonologist but also cardiologist. Early reports from China showed that cardiovascular comorbidities add more mortality than without comorbid. Cardiac implication of this infection is cardiac injury. Viral pathology and pathophysiology that induced cardiac injury is still debatable and not well understood. Angiotensin-converting enzyme 2 (ACE2) has emerged as a key regulator of renin-angiotensin system in cardiovascular disease. ACE2 has been postulated as one of the pathophysiology of COVID-19 and cardiac injury.